2016
DOI: 10.3389/fmicb.2016.00853
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Dormancy Is More Prevalent in Freshwater than Hypersaline Lakes

Abstract: Bacteria employ a diverse array of strategies to survive under extreme environmental conditions but maintaining these adaptations comes at an energetic cost. If energy reserves drop too low, extremophiles may enter a dormant state to persist. We estimated bacterial dormancy and identified the environmental variables influencing our activity proxy in 10 hypersaline and freshwater lakes across the Western United States. Using ribosomal RNA:DNA ratios as an indicator for bacterial activity, we found that the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 104 publications
1
26
0
Order By: Relevance
“…Others studies based on RNA and DNA extractions have used the RNA/DNA ratio as a proxy to investigate microbial dormancy and to estimate the metabolically active community (Aanderud et al, 2016; Jones & Lennon, 2010). In a similar way we defined the root fungal microbiome of co-occurring A. stolonifera plants by combining the DNA- and RNA-based 18S rRNA amplicon analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Others studies based on RNA and DNA extractions have used the RNA/DNA ratio as a proxy to investigate microbial dormancy and to estimate the metabolically active community (Aanderud et al, 2016; Jones & Lennon, 2010). In a similar way we defined the root fungal microbiome of co-occurring A. stolonifera plants by combining the DNA- and RNA-based 18S rRNA amplicon analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has supported the existence of such microbial seed banks: For example, multiple studies have showed that the recruitment of rare bacteria can partly explain seasonal or spatial taxonomic changes within or across communities (Campbell et al, 2011;Sjöstedt et al, 2012;Caporaso et al, 2012a;Comte et al, 2014;Shade et al, 2014;Aanderud et al, 2015;Neuenschwander et al, 2015;Ruiz-GonzĂĄlez et al, 2015;Langenheder et al, 2016;Niño-GarcĂ­a et al, 2016a). Other studies have considered the widespread dormancy found among bacteria or archaea (Jones and Lennon, 2010;Campbell et al, 2011;Hugoni et al, 2013;Aanderud et al, 2016) or the presence of core taxa that persist spatially and seasonally within or across habitat types (Caporaso et al, 2012a;Gibbons et al, 2013;Valter de Oliveira and Margis, 2015) as evidence of a seed bank. In spite of this evidence, the identification and delineation of the microbial seed bank remains difficult in practice.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pairing both 16S ribosomal transcripts (rRNA) as well as the 16S ribosomal gene (rDNA) sequencing allows for calculation of 16S rRNA:rDNA ratios, which attempts to normalize rRNA levels by the abundance of that taxon in the community and quantify its relative level of activity (8, 11, 14, 15). Taxa with 16S ratios greater than a specified threshold are considered ‘active’, and most studies report using a threshold of 1.0, which indicates more rRNA reads than rDNA reads for those taxa (6, 8, 16). One limitation to this approach is that using an arbitrary threshold to distinguish active from dormant taxa may be problematic in diverse communities (13, 17), given that rRNA production and growth rate are not necessarily always correlated (24–29).…”
Section: Introductionmentioning
confidence: 99%